Design and Assessment of a 3.7 KW Off-Grid Biogas Power System for Economic Optimization in Medium-Scale Nigerian Farming - Ignatius, Ibekwe Arinze; Sylvester, Abonyi Emeka; Muoghalu, Chidiebere Nnaedozie; Anionovo, Ugochukwu Edebeani (Asian Journal of Science, Technology, Engineering, and Art, 2026)
The removal of fuel subsidies in Nigeria in May 2023 sharply increased energy costs, with Premium Motor Spirit (PMS) and Automotive Gas Oil (AGO) prices rising by more than 200%, thereby intensifying operating cost pressures in the agricultural sector, particularly for small- and medium-scale farms dependent on fossil-fuel-based power. This study evaluates the feasibility of an off-grid biogas power system as a cost-mitigation strategy through the design, capacity optimization, and techno-economic assessment of a 3.7 kW biogas-based electricity generation system. A representative medium-scale livestock farm comprising 10 cattle, 20 pigs, and 500 poultry birds was analyzed. The proposed system integrates a 30 m³ fixed-dome anaerobic digester operating under a co-digestion regime using mixed swine, bovine, and poultry substrates, with a total daily feedstock input of approximately 235 kg. System modeling indicates a biogas production potential of 13.15 m³ per day, which, when supplied to a dual-fuel generator, produces an average electrical output of 22.35 kWh per day and supports continuous operation of a 3.7 kW load for up to six hours. The economic evaluation shows an approximately 95% reduction in monthly energy expenditure, from ₦319,000 to ₦14,000, while digestate utilization as organic fertilizer provides an additional estimated monthly revenue of ₦168,000. Financial indicators reveal a payback period of 5.5 months and a gross profit increase exceeding 100% within the first year of operation. Performance assessment further demonstrates benefits in electrical output, fossil fuel displacement, operating cost savings, investment recovery, environmental impact, and waste treatment efficiency. The study concludes that small-scale biogas power systems of this capacity are technically robust and economically viable for decentralized agricultural energy supply in Nigeria, contributing to rural energy security, emission reduction, and circular resource utilization.